Study Of The Historical Geography Of The Ancient Sughd Oasis - Khidirov Ibrokhim (Peerian Journals Publishing, 2022)
This article covers the issues of the historical geography of Sogd, which has repeatedly become the center of world civilization in the past. The author, relying on archaeological data and written sources, made clarifications in the problem on the basis of existing scientific and historical literature. He made a comparative analysis of existing specific approaches and theories on the historical geography of Sogd. As a result of the carried outresearch, the author concludes that the border of Sogd as a country in the early Iron Age could be limited to the Bukhara oasis in the West, the Gisisar mountains in the East, the lower reaches of the Kashkadarya in the south andthe Kukhitang hills as well asthe Nurota mountains in the North.
Keywords: Historical geography; archaeological data; written sources; political boundaries